ROAD-SHOULDER DETECTING DEVICE AND VEHICLE USING ROAD-SHOULDER DETECTING DEVICE - MURAMATSU SHOJI; SHIMA TAKESHI; HIGUCHI MIRAI; MONJI TATSUHIKO; NAKA TAKUYA (2012)
Disclosed is a road-shoulder detecting device including a distance-information calculating portion for calculating the presence of a physical object and the distance from the subject vehicle to the object from input three-dimensional image information relating to an environment around the vehicle, a vehicular road surface detecting portion for detecting a vehicular road surface with the subject vehicle from a distance image, a height difference calculating portion for measuring height difference between the detected vehicular road and an off-road region, and a road shoulder decision portion for deciding height difference as to whether the road shoulder is boundary between the surface and the region in a case where there is an off-road region lower than the vehicular road surface.